2008
DOI: 10.1177/104063870802000608
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Characterization of Mammary Squamous Cell Carcinoma of the Dog

Abstract: Abstract. Squamous cell carcinoma of the mammary gland is rare in both veterinary and human medicine. Whereas human metaplastic and squamous variants are known, the objectives of the current study were to ascertain the presence of such entities in canine mammary tumors and to distinguish them from other (epidermal, sweat gland) squamous tumors that may develop in the same area. A panel of antibodies (anticytokeratin [CK] 19, CK 14, CK 5/6, pancytokeratin, and vimentin) was used on 18 mammary gland malignancie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
3
6
0
Order By: Relevance
“…CK 19 has been found to detect glandular epithelial cells in canine mammary tumors. The AE3 antibody has already been used in canine tissue sections to identify the luminal epithelium of the normal mammary gland (9,27). Based on these data, our findings confirmed that antibodies "LP34" revealed negative immunostaining for metastatic glandular epithelial cells whereas antibodies "AE1/AE3" revealed strongly positive immunostaining for metastatic glandular epithelial cells in the suspected cases of metastasis of mammary tumors to the skin.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…CK 19 has been found to detect glandular epithelial cells in canine mammary tumors. The AE3 antibody has already been used in canine tissue sections to identify the luminal epithelium of the normal mammary gland (9,27). Based on these data, our findings confirmed that antibodies "LP34" revealed negative immunostaining for metastatic glandular epithelial cells whereas antibodies "AE1/AE3" revealed strongly positive immunostaining for metastatic glandular epithelial cells in the suspected cases of metastasis of mammary tumors to the skin.…”
Section: Resultssupporting
confidence: 78%
“…Similar data proving that antibodies "LP 34" confirm the epithelial origin of the glandular cells have been reported by many researchers (17,18,27).…”
Section: Resultssupporting
confidence: 77%
“…In cases of poorly differentiated carcinomas which lack morphologic features of squamous or glandular differentiation, this distinction between squamous cell carcinoma and adenocarcinoma can be difficult. Molecular methods to aid in this diagnosis specifically within the tonsil have not been investigated in veterinary species; however, similar to other anatomical locations such as the mammary gland, it is possible that positive labelling for cytokeratin19 in glandular carcinomas of the tonsil may differentiate them from squamous cell carcinoma 22 . Salivary carcinomas and oral squamous cell carcinomas with suspected metastases to the tonsil were included when histopathology was consistent with tonsillar tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Squamous pearls are poorly formed or absent. They are negative for periodic acid Schiff stain and show CK5 and CK6 8,9 positivity. p63 is a sensitive marker for metaplastic carcinomas of the breast especially the squamous type.…”
Section: Discussionmentioning
confidence: 99%